2021
DOI: 10.1080/23279095.2021.1872576
|View full text |Cite
|
Sign up to set email alerts
|

Teleneuropsychology practice survey during COVID-19 within the United States

Abstract: Objective: Identify factors influencing service delivery changes during COVID-19 and examine barriers and provider satisfaction with teleneuropsychology (teleNP). Method: Licensed clinical neuropsychologists within the United States recruited via neuropsychology-specific listservs (July-August 2020) to complete an online survey. Results: A total of 261 individuals completed the survey. Most (76%) reported delivering in-person testing in some capacity at the time of our survey. Relatively more private practitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Zoom®, Doxy.Me®, and MyChart® were the platforms used by the majority of respondents to conduct remote cognitive assessments, similar to what was found by Rochette et al (2021) in their survey study. The use of certain technologies for TeleNP was largely driven by organizational-related mandates and/or due to the HIPAA-compliant features of these technologies (see Table 2 ).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Zoom®, Doxy.Me®, and MyChart® were the platforms used by the majority of respondents to conduct remote cognitive assessments, similar to what was found by Rochette et al (2021) in their survey study. The use of certain technologies for TeleNP was largely driven by organizational-related mandates and/or due to the HIPAA-compliant features of these technologies (see Table 2 ).…”
Section: Discussionsupporting
confidence: 75%
“…We also sought information on the common strategies that TeleNP users employed to navigate the challenges associated with TeleNP use, and based on the data we have proposed some practical solutions to address specific challenges. Although a recent study by Rochette et al (2021) used a similar survey design, our study is unique because we included information not reported elsewhere, such as the inclusion of information related to the use of TeleNP for clinical versus research purposes and the reasons TeleNP users were using or switched between TeleNP technologies. We also elicited the perspectives of non-neuropsychologists in the USA (e.g., graduate students, research assistants, psychometricians) who use/used TeleNP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations